Empirical conceptualization of Customer loyalty on relationship marketing and sustained competitive advantage - Affran, Samuel; Dza, Mawuko; Buckman, Jocelene (Journal of Research in Marketing (ISSN: 2292-9355), 2019)
The relational approach to marketing sets customer loyalty as a strategic tool given that many firms have come to realize the economic importance of a loyal customer base. Most often than not financial institutions tend to depend on tangible resources to gain competitive advantage while placing less emphasis on intangible resources such as customer loyalty. Thus, the main motivation for conducting this research is to ascertain the mediating effect of customer loyalty on relationship marketing strategies and sustained competitive advantage. A questionnaire was extracted from relevant existing literature. It was administered on 300 bank relationship officers in Ghana with the underlying reason that they have what it takes to establish linkages among the various constructs. Hierarchical regression analysis was used to assess the impact of customer loyalty on relationship marketing strategies and sustained competitive advantage. The study revealed that, there is a positive relationship between research marketing strategies and sustained competitive advantage ( = .198, p< 0.131). But this impact is not significant as the significant level is 0.131, which is way above the standard significant value of 0.05. Thus, holding all other variables constant, relationship market strategies will have an impact of 19.8% on sustained competitive advantage though the impact is not significant (i.e. 0.131). The situation seems different when customer loyalty was introduced as a mediating factor. Findings show that, holding all other variables constant, customer loyalty accounts for 40.9 % change in sustained competitive advantage. In quintessence, this result proves that a unit change in customer level will induce 40.9% change in the sustenance of the banks’ competitive advantage. In other words when customer loyalty is increased by 1%, suggests that sustained competitive advantage will be increased by 40.9%. The significance level of this outcome in reference to the study results was 0.000, which is less than the typical value of 0.01 indicating that the variance between the two variables in question was perfectly significant. The study recommends to banks wishing to attain sustained competitive advantage to first focus their relationship marketing strategies on achieving customer loyalty by effectively communicating customers’ needs, exhibit high degree of professionalism in the discharge of their banking duties and be prompt in handling customers grievances.